Differentiating tardive dyskinesia: a video-based review of antipsychotic-induced movement disorders in clinical practice. (20th April 2022) - Hauser, Robert A.; Meyer, Jonathan M.; Factor, Stewart A.; Comella, Cynthia L.; Tanner, Caroline M.; Xavier, Rose Mary; Caroff, Stanley N.; Lundt, Leslie
Abstract: Accurate diagnosis and appropriate treatment of tardive dyskinesia (TD) are imperative, as its symptoms can be highly disruptive to both patients and their caregivers. Misdiagnosis can lead to incorrect interventions with suboptimal or even deleterious results. To aid in the identification and differentiation of TD in the psychiatric practice setting, we review its clinical features and movement phenomenology, as well as those of other antipsychotic-induced movement disorders, with accompanying links to illustrative videos. Exposure to dopamine receptor blocking agents (DRBAs) such as antipsychotics or antiemetics is associated with a spectrum of movement disorders including TD. The differential diagnosis of TD is based on history of DRBA exposure, recent discontinuation or dose reduction of a DRBA, and movement phenomenology. Common diagnostic challenges are the abnormal behaviors and dyskinesias associated with advanced age or chronic mental illness, and other movement disorders associated with DRBA therapy, such as akathisia, parkinsonian tremor, and tremor related to use of mood stabilizing agents (eg, lithium, divalproex). Duration of exposure may help rule out acute drug-induced syndromes such as acute dystonia or acute/subacute akathisia. Another important consideration is the potential for TD to present together with other drug-induced movement disorders (eg, parkinsonism, parkinsonian tremor, and postural tremor from mood stabilizers) in the same patient, which can complicate both diagnosis and management. After documentation of the phenomenology, severity, and distribution of TD movements, treatment options should be reviewed with the patient and caregivers.